(untitled) (World of finance, 2024)
Introduction. Settlement of the state debt problem determines the country’s budgetary capacity, the situation of its currency reserves, the level of interest rates, the investment climate, the stability of the national currency, and the behavior of all segments of the financial market. At the same time, in modern conditions, there is no unified approach to the management of the state debt as a priority direction of the state financial policy, which requires the search for opportunities to fulfill the state’s debt obligations in order to form the goals of its balanced economic development, to intensify scientific efforts aimed at researching the above-mentioned problem. The purpose of the article is to systematize approaches to determine the features of state debt management and assess its consequences for identifying balanced development of the country. Results. The problems of increasing the state’s debt obligations, which lead to structural imbalances, increase the country’s financial dependence on foreign creditors, reduce its solvency and investment attractiveness and increase debt service costs, are studied. The analysis of the conditions of formation of the state’s debt obligations was carried out and an assessment of their consequences in the context of balancing the country’s development was carried out. The peculiarities of the change in the structure of the state debt of Ukraine in terms of repayment currencies have been revealed. The indicators of Ukraine’s debt burden were monitored and compared with the limit values in order to determine the level of financial threat to the country. The consequences of an inefficient mechanism of state debt management, which are revealed at the stage of servicing and repayment of the state debt and which lead to the need for annual interest payments financed from the budget, are singled out. The measures to improve the government debt management mechanism to prevent negative macroeconomic trends are substantiated. Conclusions. According to the results of the study, it was established that the state debt of Ukraine creates risks for the financial capacity of the state, and the further attraction of loan funds at insignificant rates of economic growth increases the threats to macro-financial stability. Therefore, to increase the effectiveness of state debt management, it is important to form a proper management mechanism, monitoring of debt security indicators and determine the optimal structure of the debt-to-GDP ratio, taking into account the main aspects and trends of development of the national economy. To improve the mechanism of state debt management, it is proposed to: reduce the share of debt denominated in foreign currency; increasing the share of domestic borrowing in the structure of the state debt; reduce the specific weight of debt that must be repaid in the short term; increase the demand for government securities; refuse to attract financial resources of international organizations, which provide for additional crediting conditions and limitation of economic and political dependence of the state.